PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI UD HENNY ALUMINIUM TELUKDALAM KABUPATEN NIAS SELATAN - Herna Wati Putri Duha (Universitas Nias Raya, 2026)
This research uses quantitative research methods. This research was conducted at UD. Henny Aluminum with 33 respondents. The aim of this research is to determine the effect of price on UD consumer purchasing decisions. Henny Aluminum. This type of research is quantitative and associative by distributing questionnaires to UD consumers. Henny Aluminum Teluk in South Nias Regency. With an incidental sampling technique, the sample size was thirty-three respondents. The questionnaire was tested for validity and reliability before collecting data. From the results of data analysis carried out through partial statement items, it is stated that the price variable has a positive and significant effect on consumer purchasing decisions with a tcount of 5.397 > ttable 1.692 and a significance level of 0.000 > 0.05. Shows that the diversity of the dependent variable is explained by the independent variable 71.3% while the remaining 28.7% is a variable outside the model. Suggestions put forward to improve product purchasing decisions at UD. Henny Aluminum Teluk in South Nias Regency means that business actors should pay attention to the affordability of consumers in purchasing the products they sell.